Pemikiran dan Gerakan Politik Islam Indonesia - MHD. SYAHMINAN (Politeia: Jurnal Ilmu Politik, 2012)
There are many things that affect to the political thinking in Indonesia. Especially the muslims leader. They are strongly influenced by various types of political thought from the muslim coun-try. Middle east, India, Afrika, Turki are the source of Islamic political thought. At that place there are some thinker such as: Muhammad Rasyid Ridha, Abu Al-A’la Al-Maududy, Muham-mad Qutb, Ahmad Lufti Sayyid, Thaha Husein, Ali Abd Al- Raziq, Muhammad Abduh and Mu-hammad Hu-sein Haikal. This study describes the political thought of Islam in Indonesia and its relation to Islamic political movements. Base on data from literature and documents, this study has conclusions that Islamic political thought in Indonesia due to three factors: First, the ukhuah Islamiyah principle is the foundation of relationships in the Islamic world, also in the muslim movement; Second, anti-colonial generation is born because the influence of Islam; Third, the debate about the foundations of the country affected by Islamic political thought.Keywords: Political thinking, Islamic political thought, polical movement.